Recombinant bovine interferon gamma inhibits the growth of Cowdria ruminantium but fails to induce major histocompatibility complex class II following infection of endothelial cells - Totte, P.; Vachiery, N.; Martínez, D.; Trap, I.; Ballingall, Keith T.; MacHugh, Niall D.; Bensaid, A.; Werenne, J. (Elsevier, 1996)
Recombinant bovine IFN gamma is a potent inhibitor of Cowdria ruminantium growth in vitro irrespective of the rickettsial stock, or the origin of the endothelial cells. These results suggest an important role for IFN gamma in protective immune responses against C. ruminantium infections. Here we also show that IFN gamma can induce the expression of MHC class II molecules on the surface of endothelial cells. However, treatment of endothelial cells with IFN gamma following infection with Cowdria fails to induce MHC class II expression. The implications of this pathogen-specific effect on class II expression by endothelial cells with regard to its recognition by the host immune system are discussed.